The Role of motive in the criminalization of terrorism - حسين, كاظم عبدالله (Journal of Legal Sciences, 2019)
The roll of motive in the legal model of terrorist crimes. It's important to define the roll of motives in modern criminal policy as whole and terrorist crimes in specific Motives are important mental elements regarding the criminals, criminalization, deterrent, and criminal charges.Modern terrorist crimes are national and international immediate and dangerous threat to individuals lives, properties, and their Holly believes. Terrorists acts aimed to spreading fears, and desperation in hearts of persons and social institutions in order to enforce ideological system. This is explaining legislative attention toward Terrorists motives in the construction of criminal intent. Motives is the core of any Effective criminal justice system. And it should be indispensable part of the legal model of terrorist crimes. This is the central question of this research. In order to achieve that goal this research divided into the following:• Introduction• The first section: Concept of motive• The second section: Terrorists motives and its impact on the actus reus• The third section Terrorists motives and its impact on the mens rea.• Summary including the results and suggestions.